Theocracy in the Greater Tibetan Region: A Review of Scholarship - Deleplanque, Jetsun (Religion compass, 2025)
This article reviews the evolution of scholarly understanding regarding the integration of religious and political power in the greater Tibetan region, with particular focus on the seventeenth- and eighteenth-century period when theocratic governance crystallized under figures like the Fifth Dalai Lama Ngawang Lobsang Gyatso. The article traces how academic perspectives have shifted from early approaches—constrained by limited sources and mid-twentieth-century analytical frameworks—toward more sophisticated methodologies that engage with how Tibetans themselves conceptualized and enacted governance. The study examines how scholarship has moved toward frameworks that recognize Tibetan categories like chö (chos) and si (srid) as inextricably linked dimensions of governance. The analysis highlights how the specific formulation of chösi zungdrel (union of religious and temporal spheres) as a theory of governance emerged in the seventeenth century while drawing on centuries of earlier experimentation with religious-temporal configurations. Contemporary approaches discussed include cosmological frameworks that treat Buddhist discourse as constitutive of political reality (MacCormack's cosmo-moral order, Deleplanque's theotopia), practice-centered analyses using multilingual archives to examine how power was negotiated in practice (Tuttle, Schwieger, Oidtmann, Ishihama, Sullivan), and material studies exploring how authority was constructed through architecture, ritual and artistic production (Debreczeny, Schaeffer, Jansen, Lin). The article demonstrates how these mutually complementary methodological approaches—combining close readings of indigenous texts, archival documentation, and material analysis—offer models for understanding political systems where religious and temporal domains functioned as mutually constitutive rather than separate spheres.